IDENTIFICATION OF PHENOL COMPOUNDS OF LIQUID SMOKE SHELL OIL AT HIGH TEMPERATURE PYROLYSIS - Desi Ardilla; Muhammad Tamrin; Basuki Wirjosentono; Eddiyanto , (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The aim of this study was to determine the content of phenol in the liquid smoke palm kernel shells produced at a temperature 600ᵒC, 700ᵒC, 800ᵒC. Pyrolysis process was carried out by using a furnice that surrounding covered with fire-resistant white cement so that the smoke does not escape into the air and liquid smoke produced more leverage. Temperatures used 600ᵒC, 700ᵒC, 800ᵒC use with condenser-type spiral coil number of turns 30. Liquid smoke produced in deposited for 7 days and in the centrifuge with a rotation speed of 3800 rpm for 60 minutes, filtered and distilled at 125ᵒC temperature for 60 minutes. Liquid smoke analyzed (characterization) using GC-MS and phenol identified for each temperature 600ᵒC is 35.09%, the temperature 700ᵒC is 37.962% and 37.494% temperature 800ᵒC is.Keywords: Liquid Smoke, Phenol compounds, GC-MS